Further Consideration of a New Liquidity Instrument for Market Access Countries : Design Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper focuses on a specific set of issues -- qualification criteria, monitoring structure, access levels and terms, links to other Fund facilities, and links to the private sector. This paper is a complement and follow-up to an earlier paper, which itself considered the broader issues involved in creating a new instrument. The paper does not put forward a concrete proposal to Directors, but seeks to achieve a further convergence of views on these key issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet